Exosomal miR-21-5p from ectopic endometrial stromal cells drives fibrosis progression in endometriosis through direct VHL targeting - Jia-Hao Chen; Yi-Hong Lei; Dian-Chao Lin; Hua-Ying Zhang; Zhi-Xiong Huang; Ruo-Fan Huang; Pei-Tong Wei; Meng-Jie Yang; Xin-Yu Ding; Wei-Dong Zhou; Qiong-Hua Chen (Human Cell, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

A Human-Ocean Health Index (HOHI) for integrated assessment under the cumulative effects of human activities and global change - Suzhen Yang; Qinhua Fang; Ruiqing Qin; Lin Liang; Wenyan Tang; Dian Zhang; Zhiyi Kan; Lusita Meilana; Huiling Liu (Marine Pollution Bulletin, 2026)

Rapid and high-capacity adsorption of malachite green based on recoverable amino-modified HOF systems - Yile Jiang; Xinyan He; Ruiqi Zhu; Qiuxia Wu; Lin Zhang; Yabing He; Dian Zhao (Journal of Environmental Sciences, 2026)

Detecting global ocean subsurface density change with high-resolution via dual-task densely-former - Hua Su; Weiqi Xie; Luping You; Sihui Li; Dian Lin; An Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Functional Analysis of the mstn1 Gene and Its Transcriptional Regulation by Mef2 Factors in Yellowfin Seabream, Acanthopagrus latus (Hottuyn, 1782) - Hong-Xi He; Ke-Cheng Zhu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Lin Xian; Teng-Fei Zhu; Dian-Chang Zhang; Min Yang (Fish Physiology and Biochemistry, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Bi-coupled discontinuous Galerkin method for realizing large-scale 3-D random fields with non-separable autocorrelation functions - Xin Lin; Xiao-Song Tang; Dian-Qing Li; Shun Wang (Computers and Geotechnics, 2025)

Transcriptomic and Metabolomic Analyses Provide Insights into Cryptocaryon irritans Resistance in Golden Pompano (Trachinotus ovatus) - Bo Liu; Bao-Suo Liu; Jing-Wen Yang; Hua-Yang Guo; Nan Zhang; Teng-Fei Zhu; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fishes, 2025)
Golden pompano (Trachinotus ovatus) is an economically important fish species along China’s southern coast. However, infections by Cryptocaryon irritans severely constrain the healthy and sustainable development of the aquaculture industry. To investigate the genetic basis of resistance to this parasite in golden pompano, this study employed transcriptomic and metabolomic analyses to compare differences between susceptible (ES) and resistant (RS) groups following C. irritans challenge. Transcriptome analysis identified 2031 differentially expressed genes (DEGs) between EST and RST groups, comprising 1004 up-regulated and 1027 down-regulated genes. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment revealed that these DEGs were primarily enriched in lipid metabolism and amino acid metabolism pathways. Untargeted metabolomics detected 461 significantly differentially abundant metabolites (295 up-regulated, 166 down-regulated), confirming pronounced metabolic differences between ES and RS groups, particularly in lipid and amino acid metabolism. Further, KEGG enrichment highlighted steroid hormone biosynthesis, α-linolenic acid metabolism, and arachidonic acid metabolism as the most significantly altered pathways upon infection. This integrated transcriptomic and metabolomic study reveals substantial differences in gene expression and metabolite profiles between susceptible and resistant golden pompano in response to C. irritans. These changes predominantly involve lipid metabolism and amino acid metabolism, suggesting that these processes are critical in determining host resistance/susceptibility.

Humic acid and ferrihydrite weaken Cd release and resupply in high geological background soil assessed by DGT-DIFS - Dongqin LI; Zhendong PENG; Chunyan LIU; Yongtao LI; Jinjin WANG; Zhichao WU; Qinghui LIU; Furong LI; Hanzhi SHI; Dian WEN; Huayi CHEN; Xu WANG; et al. (Pedosphere, 2025)

Developing a digital twin for dam safety management - Shao-Lin Ding; Jia-Jun Pan; Yanli Wang; Han Xu; Dian-Qing Li; Xin Liu (Computers and Geotechnics, 2025)

Gut microbiome composition likely affects the growth of Trachinotus ovatus by influencing the host's metabolism - Chen-Xu Wu; Bao-Suo Liu; Hua-Yang Guo; Teng-Fei Zhu; Lin Xian; Nan Zhang; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Review and prediction: Carbon emissions from the materialization of residential buildings in China - Xing Xiong; Xiaojun Li; Shaobo Chen; Dian Chen; Jinchen Lin (Sustainable Cities and Society, 2025)

Deciphering Trachinotus ovatus resistance to Streptococcus agalactiae:GWAS identification of key SNPs and candidate genes - Yi-Yao Sun; Jie Gao; Bao-Suo Liu; Nan Zhang; Hua-Yang Guo; Ke-Cheng Zhu; Lin Xian; Dian-Chang Zhang (Aquaculture, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

SNPs in the Galectin-8 gene of Acanthopagrus latus have been found to be associated with resistance trait to Streptococcus iniae - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Characterization of the Galectin-3 gene and its association with Streptococcus iniae resistance traits in Acanthopagrus latus (Houttuyn, 1782) - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Folding of a single layer in an anisotropic viscous matrix under layer-parallel shortening - Yuan-bang Hu; Paul D. Bons; Tamara de Riese; Shu-gen Liu; Maria-Gema Llorens; Eloi González-Esvertit; Enrique Gomez-Rivas; Dian Li; Yu-zhen Fu; Xue-lin Cai (Journal of Structural Geology, 2024)

Genomic Investigation of a Rhizosphere Isolate, Streptomyces sp. JL1001, Associated with Polygonatum cyrtonema Hua - Lin Jiang; Zixian Zeng; Zhi Wang; Min Tang; Sai Jiang; Qingxian Ma; Zhong Wang; Dian Peng; Shunxiang Li; Hong Pu (Current Microbiology, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Practical copula-based FORM for efficient slope reliability analysis involving correlated non-normal variables - Xiao-Song Tang; Xin Lin; Dian-Qing Li; Shun Wang (Computers and Geotechnics, 2024)

Genomic structures of insulin-like growth factor from golden pompano (Trachinotus ovatus) and their expression responses to the feed types - Bo Liu; Yin-Yin Liang; Hua-Yang Guo; Bao-Suo Liu; Jing-Wen Yang; Nan Zhang; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fish Physiology and Biochemistry, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

Cryopreservation of Goldlined seabream Rhabdosargus sarba (Forsskål, 1775) sperm: CASA observation and enzyme activity evaluation - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Aquaculture, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Genome-wide identification of heat shock protein gene family and their responses to pathogen challenge in Trachinotus ovatus - Yi-Yao Sun; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Ke-Cheng Zhu; Lin Xian; Peng-Hai Zhao; Hui-Yuan Yang; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

A change in substance and microbial community structure during the co-composting of kitchen waste anaerobic digestion effluent, sewage sludge and Chinese medicine residue - Dian Li; Wei Jiang; Yuanyao Ye; Jiwu Luo; Xiaojuan Zhou; Lin Yang; Gang Guo; Songlin Wang; Zizheng Liu; Wenshan Guo; Huu Hao Ngo (Science of The Total Environment, 2024)

Yellow pigments produced by oxidative oligomerization of dihydrochalcone glucoside and the reaction mechanism - Zhang-Bin Liu; Yosuke Matsuo; Yoshinori Saito; Yong-Lin Huang; Dian-Peng Li; Gen-ichiro Nonaka; Takashi Tanaka (Food Chemistry, 2023)

Cryopreservation of black seabream (Acanthopagrus schlegelii) sperm - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Theriogenology, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

A combined passivator of zeolite and calcium magnesium phosphate fertilizer: Passivation behavior and mechanism for Cd (II) in composting - Wei Jiang; Dian Li; Junlin Yang; Yuanyao Ye; Jiwu Luo; Xiaojuan Zhou; Lin Yang; Zizheng Liu (Environmental Research, 2023)

Study on the chemical composition of Caesalpinia sinensis - Lu-Fen Leng; Qi Lai; Dian Lv; Jun-Lin Yin; Guang-Zhi Zeng (Natural Product Research, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Two-stage Bayesian experimental design optimization for measuring soil–water characteristic curve - Shao-Lin Ding; Dian-Qing Li; Zi-Jun Cao; Wenqi Du (Bulletin of Engineering Geology and the Environment, 2022)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Analysis of Meteorological Drought Resilience and Risk Assessment of Groundwater Using Signal Analysis Method - Yuan-Chien Lin; En-Dian Kuo; Wan-Ju Chi (Water Resources Management, 2021)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Five macrocyclic glycosides from Schoenoplectus tabernaemontani - Dian Peng; Xiaolin Lin; Lin Jiang; Juan Huang; Guangyao Zeng; Xu Deng; Yingjun Zhou (Natural Product Research, 2019)

Phylogeographic analysis of porcine reproductive and respiratory syndrome virus 1 in Guangdong province, Southern China - Shao-Lun Zhai; Tao Lin; Xia Zhou; Zhang-Fu Pei; Zu-Zhang Wei; He Zhang; Xiao-Hui Wen; Qin-Ling Chen; Dian-Hong Lv; Wen-Kang Wei (Archives of Virology, 2018)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Species-specific effects of leaf litter on seedling emergence and growth of the invasive Flaveria bidentis and its co-occurring native species: a common garden test - Ke-li Li; Hui-yan Li; Chao-he Huangfu; Dian-lin Yang; Hong-mei Liu; Hui Wang (Plant Ecology, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

Emergence of reticuloendotheliosis virus in pigeons in Guangdong Province, Southern China - Shao-Lun Zhai; Sheng-Nan Chen; Tao Lin; Xiao-Hui Wen; Wen-Kang Wei; Dian-Hong Lv; Rui-Ai Chen (Archives of Virology, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

New sesquiterpenoid derivatives from Solanum septemlobum with cytotoxicities - Lei Zhang; Hai-Qing Lin; Gui-Sheng Li; Xi-Dian Yue; Sheng-Jun Dai (Natural Product Research, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Improved Euler method for the interpretation of potential data based on the ratio of the vertical first derivative to analytic signal - Can-Can Guo; Sheng-Qing Xiong; Dian-Jun Xue; Lin-Fei Wang (Applied Geophysics, 2014)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Genomic sequencing and analysis of Chilli ringspot virus, a novel potyvirus - Dian Gong; Jian-Hua Wang; Zhan-Song Lin; Shao-Yan Zhang; Yu-Liang Zhang; Nai-Tong Yu; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

A STELLA model for the estimation of atrazine runoff, leaching, adsorption, and degradation from an agricultural land - Ying Ouyang; Jia En Zhang; Dian Lin; Guo Dong Liu (Journal of Soils and Sediments, 2010)

Effect of bilateral in vivo ischemia/reperfusion on the activities of superoxide dismutase and catalase: Response to a standardized grape suspension - Alpha Dian-Yu Lin; Anita Mannikarottu; Barry A. Kogan; Catherine Whitbeck; Robert E. Leggett; Robert M. Levin (Molecular and Cellular Biochemistry, 2007)